Biomass estimation and physicochemical characterization of winter vine prunings in the Chinese and global grape and wine industries. (1st March 2020) - Sun, Xiangyu; Wei, Xiaofeng; Zhang, Junxiang; Ge, Qian; Liang, Yanying; Ju, Yanlun; Zhang, Ang; Ma, Tingting; Fang, Yulin
Graphical abstract: Highlights: First report evaluating the WVPs yields in China and global grape and wine industries. Table grape higher than wine grape, pergola systems higher than hedge systems. Older vines showed higher WVP yields than younger vines. Average WVP yield in China was 2.35 kg/tree FW with a range of 1.33–3.21 kg/tree FW. WVP yield 42.31 million ton FW in global and 6.04 million ton FW in China in 2017. Abstract: The residual biomass of winter vine prunings (WVPs) in the Chinese and global grape and wine industries was investigated and estimated, and the physicochemical characteristics of Chinese WVPs were analyzed. The eight regions investigated within China showed a total annual regional WVP yield of 201–842 kt FW, with R1 and R6 region showing the highest and the lowest region yields, respectively. The R4 and R2 regions showed the highest and the lowest yield per tree. Table grapes showed considerably higher WVP yields than wine grapes, whereas the pergola systems showed considerably higher WVP yields than the hedge systems. In addition, older vines showed higher WVP yields than younger vines. Overall, the average WVP yield in China was 2.35 kg/tree FW with a range of 1.33–3.21 kg/tree FW. Globally, the estimated WVP yield has decreased gradually from 2000 to 2017 to 42.31 million ton FW; in contrast, estimated WVP yield in China has increased substantially over the same period to 6.04 million ton FW. Winter vine pruning was the leading source of solid grape waste in the grape and wine industry, both absolutely and proportionally, and was characterized by such properties as a high dry matter content, mild acidity, high levels of organic matter and nutrients, and low fat. It is clear that WVP represents a resource of immense value for generating additional wealth in China and in the global grape and wine industry.